Police responsiveness into behavioural health crisis - Ch’ng, Xin Hwa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Law enforcement, the representative image of the official power among the public and community, is important to maintain its integrity and legality when executing its power enshrined by the laws. Yet, the debate regarding the abuse of the police power had gained tremendous mistrust within the community, flagging the insensitiveness of the law enforcement in handling suspects who are vulnerable upon arrest. This could be detrimental to build up the integrity and the accountability of the police in the eyes of the public. The purpose of this article seeks to propose a proactive alternative that could be utilized to manage the incidence of behavioural health crisis of arrested persons more effectively and efficiently. In achieving this objective, the criminal procedure in Malaysia is discussed. This is followed by a doctrinal analysis on the manner of the arrest required for the responsiveness into behavioural health crisis. It is observed that the outreach of procedural justice into the suspects who are mentally vulnerable is not in the common address within our existing criminal procedure. A conclusion could be outlined that a proactive alternative is arguably crucial to improve the existing circumstances. The intervention is expected to be a novel approach to improve the literacy of the law enforcement with behavioural health crisis which includes the criminal procedural justice to be addressed effectively and efficiently.